Theoretical and experimental researches on fracture toughness for bedded shale using the centrally cracked Brazilian disk method with acoustic emission monitoring - Zheng, Kun; Wang, Chaolin; Zhao, Yu; Bi, Jing (Theoretical and applied fracture mechanics, 2023)
•The fracture toughness (KIc, KI + II, and KIIc) for the CCBD bedded shale are investigated using the AE technique.•The fracture criteria (MTS, MTSN, and MTSEDF) are applied to predict the fracture toughness.•The proposed k-means clustering method succeeds in identifying the specific fracture modes for the CCBD bedded shale. To investigate the fracture toughness including pure mode I, combined mode I + II, and pure mode II, the CCBD (centrally cracked Brazilian disk) fracture experiments with acoustic emission (AE) detecting are conducted on the shale specimens with distinct bedded inclination angles (0°, 30°, 60°, and 90°), and this research first introduces the detailed derivations on the three dominating fracture criteria. The investigated results demonstrate that the fracture resistances for the tested CCBD shale are insensitive to the bedded direction and the anisotropy of the fracture toughness is regarded as relatively weak, which is reflected in the smoother and more regular rupturing paths. The improved criteria (GMTS, GMTSN, and GMTSEDF) can provide a reasonable agreement with the measured data by considering the variable damaged radius of microcracking zone. The proposed k-means clustering method succeeds in identifying the specific fracture modes for the tested CCBD bedded shale in conjunction with the KDE (kernel density estimation) method, whereas the conventional AE parameter (RA and AF) method fails to analyze the fracture mechanisms.